Rhabdomyolysis triggered by iatrogenic hypothyroidism (Portuguese Journal of Family Medicine and General Practice, 2022)
Introduction: Rhabdomyolysis is a syndrome with multiple etiologies. The family physician (FP) can contribute to its investigation and to the health care articulation of the patients who suffer from it. Good access to health care and diagnostic tests are also important.Case description: Female patient, 50 years old, with a history of hypertension and hyperthyroidism treated with radioactive iodine. At the beginning of 2019, she had three appointments with other doctors due to prolonged myalgia. On June 11th she goes to the emergency department (ER) complaining of anasarca, thoracic pain, and dyspnea being diagnosed with rhabdomyolysis. She was discharged for follow-up with her FP, who consults her on June 26th and asks for blood tests and an echocardiogram. She was diagnosed with iatrogenic hypothyroidism caused by radioactive iodine therapy. After discussing the case with the Endocrinology through a phone call, she started taking levothyroxine. In her follow-up appointment with her FD on July 17th, she still complains of anasarca and dyspnea. Crackles are heard on her lung auscultation. She didn’t have the economic capacity to perform an NT-Pro-BNT to exclude acute heart failure because it wasn’t a reimbursed exam. She was referred to the ER, after discussing the case through telephone with the attendant doctor, where the NT-Pro-BNP assessment was normal, ruling out this diagnosis. She maintained treatment with levothyroxine but had a slow recovery.Comment: This case shows the obstacles that still exist in the accessibility to health care and the delay on the requirement of diagnostic tests which led to a late diagnosis. Being in touch through telephone with other health care entities made the process easier. The unavailability of NT-Pro-BNP testing in primary care led to an ER referral that could have been prevented.
Keywords: Hypothyroidism; Iatrogenic disease; Family practice; Rhabdomyolysis; Myxedema